PHYTOCHEMICAL AND MICROBIOLOGICAL ASPECTS OF THE NIGELLA SATIVA L. HERBS STUDY - A. R. Mubinov; V. A. Kurkin; E. V. Avdeeva; S. D. Kolpakova; A. V. Zhestkov (Фармация и фармакология (Пятигорск), 2022)
Nigella sativa L. is a promising plant object, herbal medicinal raw materials of which can be comprehensively used for the development of drugs with an antimicrobial activity.The aim of the study was to screen and compare the antimicrobial activity of water-ethanolic extractions from the Nigella sativa L. herbs with a eucalyptus tincture of as a reference preparation.Materials and methods. Chromatograms of the extracts were obtained by thin layer chromatography in the system of chloroform – ethanol – water (26:16:3). The detection of adsorption zones was carried out in daylight, in the UV light at λ=254 nm and λ=365 nm, as well as by treatment with reagents – a 3% alcohol solution of aluminum chloride and a solution of diazobenzosulfonic acid in a 20% sodium carbonate solution. The next step was to determine the minimum inhibitory concentration by the method of double serial dilutions in Mueller-Hinton nutrient broth (Bio-Rad, USA). As test cultures, the strains of the American Type Culture Collection (ATCC) microorganisms were used: Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), as well as Candida albicans (a clinical strain). Simultaneously, an experiment to establish a “negative” control was carried out. For the comparative evaluation of the studied samples activity, its activity was compared with the reference preparation with a proven antimicrobial activity – a eucalyptus tincture.Results. For all water-ethanolic extractions and the Nigella sativa L. herb tincture, the adsorption zones characteristic of flavonoids with Rf1 = 0.28, Rf2 = 0.15, Rf3 = 0.11 were revealed, and under the action of an alcoholic solution of aluminum chloride, the fluorescence of the adsorption zones was also enhanced, which indicates the phenolic nature of these compounds.In the course of the study, it was found out that all water-ethanolic extractions from the Nigella sativa L. herbs have the greatest antimicrobial effect against the Pseudomonas aeruginosa strain. When compared with the reference preparation – a eucalyptus tincture, it was notified that the specified tincture of the Nigella sativa L. herbs has an advantage in the antimicrobial activity over the strain of Pseudomonas aeruginosa – the action at the 16-fold dilution vs the 4-fold dilution. The action on the Escherichia coli and Candida albicans strains is comparable for the both tinctures.Conclusion. The obtained results of phytochemical and microbiological analyses will be used as a rationale for the introduction of antimicrobial preparations based on the Nigella sativa herbs in medical and pharmaceutical practice.